Reemergence of dengue virus in Bangladesh: Current fatality and the required knowledge - Rashed Noor (Tzu Chi Medical Journal)
The current fatality of dengue among the Bangladeshi population has drawn the interest of the public health professionals primarily to focus on the environmental, social, and clinical reasoning as well the possible remedies. This year, in 2019, the dengue situation in Bangladesh has appeared with all its dreadful effects leading to the highest death cases due to dengue virus (DENV) infection. According to the Directorate General of Health Services report, this year (2019) the number of DENV-infected people has appeared to be around five times higher (approximately 50,000 cases so far) compared with the last year, 2018 (around 10,000 cases). The present review discussed the current epidemics of dengue infection in Bangladesh as well the possible means of disease curing in terms of general preventive concepts. However, besides the precise treatment of the dengue-affected patients, the knowledge on DENV genome and on the protective immunity against such reemerging disease is essential.